Constraints on Olivine Deformation From SKS Shear‐Wave Splitting Beneath the Southern Cascadia Subduction Zone Back‐Arc. (19th November 2021) - Löberich, E.; Long, M. D.; Wagner, L. S.; Qorbani, E.; Bokelmann, G.
Abstract: Shear‐wave splitting observations of SKS and SKKS phases have been used widely to map azimuthal anisotropy, as caused by the occurrence of olivine, to constrain the dominant directions of upper mantle deformation. While SK(K)S splitting measurements at individual seismic stations are often averaged before interpretation, it is useful to consider additional information, for example, based on the variation of splitting parameters with azimuth due to the non‐vertical incidence of core‐phases. These constraints in theory enable a differentiation between various types of olivine and may allow us to infer otherwise poorly known upper mantle parameters such as stress, temperature, and water content. In this study, we predict the azimuthal variation of splitting parameters for A‐, C‐, and E‐type olivine fabrics and match them with observations from the High Lava Plains, Northwestern Basin and Range, and Western Yellowstone Snake River Plain in the Pacific Northwest US. This helps to constrain the amount of water in the upper mantle in the back‐arc of the Cascadia subduction zone, known for its consistent E‐W oriented seismic anisotropy, and particularly large splitting delay times. Our investigation renders the C‐type olivine mechanism improbable for this location; A‐ and E‐type fabrics match the observations, although differentiating between them is difficult. However, the agreement of the amplitude of backazimuthal variation of the fast orientation, plus the potential to explain large splitting delay times, suggest the occurrence of E‐type olivine, and thus the likely presence of a moderately hydrated upper mantle beneath Cascadia's back‐arc. Plain Language Summary: Seismic anisotropy can elucidate upper mantle deformation. Lattice‐preferred orientation of minerals such as olivine leads to shear‐wave splitting that can be observed; it is related to the character of the deformation, e.g., the olivine fabric type. Since the occurrence of A‐, C‐ and E‐type relates to the amount of water, distinguishing these fabric types is particularly interesting. Yet, it has been difficult to differentiate between them so far due to similar shear‐wave splitting they give rise to. Previous studies have not considered the slight dependence of the fast orientation with respect to the azimuth of the seismic arrival, which allows such a distinction in principle. Here, we study the E‐W pattern of fast orientations in the southern Cascadia subduction zone back‐arc, a region known for strong splitting. The comparison between observations and expectations shows that C‐type cannot be present there. Since A‐ and E‐type lead to similar fast orientations, distinguishing them is not trivial. Yet, the better fit between prediction and observation favors the presence of E‐type fabric; an argument for the strong splitting and a moderately hydrated upper mantle beneath the study area. Key Points: Shear‐wave splitting through A‐, C‐, and E‐type olivine at upper mantle conditions shows azimuthal variations that differ A‐ and E‐type reproduce polarity of observed fast orientation variation, with E‐type predicting stronger delay times E‐type olivine occurrence suggests a moderately hydrated asthenosphere in the Cascadia subduction zone back‐arc